Comparison of Voltammetric Techniques for Ammonia Sensing in Ionic Liquids - Hussain, Ghulam; Silvester, Debbie (Wiley - VCH Verlag GmbH & Co. KGaA, 2018)
© 2018 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim. In electroanalytical chemistry, it is often observed that square wave voltammetry (SWV) and differential pulse voltammetry (DPV) are more sensitive techniques compared to linear sweep voltammetry (LSV), due to their method of sampling which minimises the charging current (non-faradaic processes). In this work, a comparison of the three techniques (LSV, DPV and SWV) is performed for ammonia (NH 3 ) gas oxidation (a chemically and electrochemically irreversible redox process) in an ionic liquid over a concentration range of 10–100 ppm. Four different platinum electrodes are employed: a screen-printed electrode (SPE), a thin-film electrode (TFE), a microarray thin-film electrode (MATFE) and a Pt microdisk electrode (µ-disk). Calibration plots (current vs concentration) for all three different electrochemical techniques on all four surfaces showed excellent linearity with increased concentrations of NH 3 gas and relatively low limits of detection (LODs). On the larger mm-sized surfaces (SPE and TFE), the current responses for LSV and SWV were quite similar, but DPV gave the lowest currents. Whereas for the smaller micron sized electrodes (MATFE and µ-disk), currents were of the order LSV > SWV > DPV, with LSV being far superior to the pulse techniques. These findings suggest that the pulse techniques of SWV and DPV may not be the optimum methods, particularly on microelectrodes, for the detection of analytes such as ammonia in RTILs.